Synergizing sugarcane waste valorization: Optimization of two-stage anaerobic co-digestion for enhanced methane recovery and organic matter removal - Ribeiro, Alexandre Rodrigues; Devens, Kauanna Uyara; Camargo, Franciele Pereira [UNESP]; Sakamoto, Isabel Kimiko; Varesche, Maria Bernadete Amâncio; Silva, Edson Luiz (Elsevier, 2024)
Multiple strategies have been used in anaerobic digestion of effluents aiming to enhance the efficiency of the methane (CH4) recovery process, where co-digestion and the two-stage process emerge as prominent methods. In this context, this study aimed at evaluating the co-digestion of sugarcane vinasse and molasse in a two-stage process using anaerobic fluidized bed reactors (AFBR), verifying the effect of increasing the organic loading rate (OLR) (5–22.5 kg COD.m−3.d−1) and temperature in the second stage methanogenic reactor. Regarding the two-stage process, sugarcane vinasse and molasses fermentation demonstrated the maximum energy potential (E.P) of 57.08 kJ.d−1 (7.5 g COD.L−1). Regarding the methanogenic sequential reactors, organic matter removal reached high values (up to 84.5 % in a thermophilic sequential reactor (TSR); up to 84.5 % in a mesophilic sequential reactor (MSR)). The highest CH4 yield (MY) of 306.77 ± 38.84 mL CH4.g−1 COD rem was observed in MSR (9 kg COD.m−3.d−1). Meanwhile, the maximum value of MPR (3.8 ± 0.5 L CH4.L−1.d−1) was observed in TSR (21 kg COD.m−3.d−1). Regarding the Archaea domain, a predominance of hydrogenotrophic microorganisms could be identified, in which the genera Methanobacterium and Methanothermobacter were the most abundant in MSR and TSR, respectively. This study demonstrates that anaerobic digestion of sugarcane vinasse and molasses enhances anaerobic treatment using two-stage AFBRs. It not only produces CH4 but also generates hydrogen and high-value products through an acidogenic reactor. This research marks a significant advancement in managing sugarcane processing by-products, offering promising approaches to maximize biogas production and improve pollutant removal efficiency.
Keywords: Anaerobic biorefinery; Metabolic pathways; Metabolic prediction; Renewable energy; Temperature effects